Trade, FDI, Growth and Poverty in Bolivia - Lykke E. Andersen; Osvaldo Nina; Dirk Willem te Velde (Institute for Advanced Development Studies (INESAD), 2004)
After several decades of state-capitalism characterized by import substitution policies, Bolivia implemented in 1985 a New Economic Policy (NEP) following neo-liberal ideas of free trade, privatization, and liberalization of capital flows. It was hoped that the opening up of the economy would attract foreign direct investment (FDI) which in turn would help modernize Bolivian industry, improve productivity, increase exports, stimulate growth, and reduce poverty. This paper investigates to what extent this actually happened
Keywords: F16; 330; Trade; Foreign Direct Investment; Poverty; Inequality; Bolivia